PERFORMANCE OF SUGARCANE CULTURE PRODUCTION IN THE MAIN PRODUCING STATES - Alves, Lazaro Quintino; Franco, Petrus Narciso; Zanetti, Willian Aparecido Leoti; Góes, Bruno César (Revista Brasileira de Engenharia de Biossistemas, 2021)
The cultivation of sugarcane is one of the main sources for the production of sugar and ethanol in Brazil, measuring growth in the sector, especially after the regulation of flexfuel motor vehicles. In this sense, the objective of this work was to analyze the performance of the sugarcane cultivated area in the main producing states: São Paulo, Goiás, Minas Gerais and Mato Grosso do Sul. considered the period between 2000 and 2020; for ethanol and sugar production, the period between 2005 and 2020 was considered. Statistical analysis of the Pearson correlation (r) was performed between the studied variables, during the period from 2005 to 2020. In this sense, it was possible to observe the increase of the planted area in the analyzed regions, as well as the increase in the productivity of the crop and of the sugar-alcohol sector, mainly in the region of the Polygon of Agrohidronegócio, in the Center-South region of Brazil. Ethanol production showed growth over the period analyzed, influenced by the increase in the production of flexfuel vehicles.